Meniscal Injuries Management and Surgical Techniques - Kelly, IV, John D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Thoroughly discussing the varied elements of meniscal damage and repair, Meniscal Injuries: Management and Surgical Techniques includes the insights and expertise of over 20 leading surgeons and researchers on topics ranging from meniscal anatomy, physical examination, innovative resection and repair techniques, gene therapy, and tissue regeneration. This treatise offers wisdom aimed at assessing true surgical candidates, exploring the intricacies of meniscal composition and function, an overview of meniscal scaffolds and replacements, and patient examination pearls. Also discussed in depth is cutting edge research concerning meniscal repair enhancement, nanofiber technology as a means of meniscal replacement, and biologic agents directed toward chondral protection. All the science presented will direct the sports medicine practitioner to state-of-the-art treatment aimed at knee preservation. Meniscal repair and regeneration is a rapidly evolving science - early attempts at meniscal restoration or repair resulted in short-term gains which often sacrificed long-term joint integrity. Now, the practitioner is afforded numerous means of retaining or restoring meniscal tissue. Breakthroughs in scaffold and allograft replacement, as featured herein, offer the promise of articular cartilage preservation like never before. In addition, tissue regeneration and gene therapy techniques, featured throughout, offer a glimpse into emerging technologies aimed at preserving or replacing meniscal tissue in previously considered (3z(Bhopeless(3y (Bcases. As such, Meniscal Injuries will be an indispensible resource to orthopedic surgeons and sports medicine practitioners interested in providing the absolute most contemporary and evidence-based care to their patients.s
Meniscal Anatomy -- Physical Examination for Meniscus Tears -- Imaging of Meniscus Pathology -- Menisectomy: The Basics -- Meniscus Allograft Transplantation -- Meniscal Scaffolds: Options Post-Menisectomy -- Meniscal Repair Techniques -- Meniscal Posterior Root Tear -- Indications for Meniscus Repair -- Basic Science of Meniscus Repair: Limitations and Emerging Strategies -- Biological Augmentation of Meniscus Repair and Restoration -- Rehabilitation Following Meniscus Repair.
Keywords: Medicine; Orthopedic surgery; Sports medicine; Endoscopic surgery; Medicine & Public Health; Surgical Orthopedics; Sports Medicine; Minimally Invasive Surgery